2023
DOI: 10.4178/epih.e2023026
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in clinical biomarkers of cardiometabolic diseases by changes in exercise behavior, and network comparisons: a community-based prospective cohort study in Korea

Abstract: OBJECTIVES: Lifestyles, including exercise behaviors, change continually over time. This study examined whether the clinical biomarkers (CBs) related to cardiometabolic diseases (CMDs) and their relationships differed with changes in exercise behavior. METHODS: The Ansan-Ansung cohort study (third to fifth phases; n=2,668) was used in the current study. Regular exercise behavior was investigated using a yes/no questionnaire. Changes in exercise behavior were classified into 4 groups: Y-N, N-Y, Y-Y, and N-N, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…A number of epidemiological studies have shown the associations between PA and decreased risk of death and chronic diseases [ 10 , 11 ]; however, biological processes and the underlying mechanisms for the benefit of PA are still unclear [ 14 ]. Recently, studies have been conducted to understand the benefits of PA more thoroughly way by using not only various anthropometric and blood biomarkers [ 15 , 16 ] but also metabolites [ 17 , 18 ] and microbiomes [ 19 , 20 ]. PA induces changes in various objective measurements and clinical biomarkers in a health-promoting direction such as reducing levels of triglyceride, total cholesterol, blood glucose, and insulin, waist circumference, and body fat, while increasing HDL and muscle mass [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of epidemiological studies have shown the associations between PA and decreased risk of death and chronic diseases [ 10 , 11 ]; however, biological processes and the underlying mechanisms for the benefit of PA are still unclear [ 14 ]. Recently, studies have been conducted to understand the benefits of PA more thoroughly way by using not only various anthropometric and blood biomarkers [ 15 , 16 ] but also metabolites [ 17 , 18 ] and microbiomes [ 19 , 20 ]. PA induces changes in various objective measurements and clinical biomarkers in a health-promoting direction such as reducing levels of triglyceride, total cholesterol, blood glucose, and insulin, waist circumference, and body fat, while increasing HDL and muscle mass [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies have been conducted to understand the benefits of PA more thoroughly way by using not only various anthropometric and blood biomarkers [ 15 , 16 ] but also metabolites [ 17 , 18 ] and microbiomes [ 19 , 20 ]. PA induces changes in various objective measurements and clinical biomarkers in a health-promoting direction such as reducing levels of triglyceride, total cholesterol, blood glucose, and insulin, waist circumference, and body fat, while increasing HDL and muscle mass [ 15 , 16 ]. The influence of PA on the metabolome shows a positive association with TCA cycle metabolites, including lactate, pyruvate, and ketones.…”
Section: Introductionmentioning
confidence: 99%